Multicentre propensity score-matched study of laparoscopic versus open repeat liver resection for colorectal liver metastases. Issue 6 (1st February 2019) - van der Poel, M J; Barkhatov, L; Fuks, D; Berardi, G; Cipriani, F; Aljaiuossi, A; Lainas, P; Dagher, I; D'Hondt, M; Rotellar, F; Besselink, M G; Aldrighetti, L; et al.
Abstract: Background: Repeat liver resection is often the best treatment option for patients with recurrent colorectal liver metastases (CRLM). Repeat resections can be complex, however, owing to adhesions and altered liver anatomy. It remains uncertain whether the advantages of a laparoscopic approach are upheld in this setting. The aim of this retrospective, propensity score-matched study was to compare the short-term outcome of laparoscopic (LRLR) and open (ORLR) repeat liver resection. Methods: A multicentre retrospective propensity score-matched study was performed including all patients who underwent LRLRs and ORLRs for CRLM performed in nine high-volume centres from seven European countries between 2000 and 2016. Patients were matched based on propensity scores in a 1 : 1 ratio. Propensity scores were calculated based on 12 preoperative variables, including the approach to, and extent of, the previous liver resection. Operative outcomes were compared using paired tests. Results: Overall, 425 repeat liver resections were included. Of 271 LRLRs, 105 were matched with an ORLR. Baseline characteristics were comparable after matching. LRLR was associated with a shorter duration of operation (median 200 (i.q.r. 123–273) versus 256 (199–320) min; P < 0·001), less intraoperative blood loss (200 (50–450) versus 300 (100–600) ml; P = 0·077) and a shorter postoperative hospital stay (5 (3–8) versus 6 (5–8) days; P = 0·028). Postoperative morbidity and mortality rates were similar after LRLR and ORLR. Conclusion: LRLR for CRLM is feasible in selected patients and may offer advantages over an open approach. Graphical Abstract: Repeat liver resection is a challenging procedure and the role of laparoscopy remains unclear. This retrospective propensity score-matched study aimed to compare the short-term outcomes of laparoscopic versus open repeat liver resection. Feasible in selected patients